Insights Into Instructorsâ€™ Verbal Aggressiveness and Studentsâ€™ Machiavellianism Through Leadership Style and Motivational Climate - Bekiari, Alexandra (European Scientific Journal, ESJ, 2016)
The aim of the present study was threefold: a) to explore the relationship between perceived instructor verbal aggressiveness, leadership style, motivational climate and student Machiavellianism, b) to investigate the influence of instructor verbal aggressiveness on their leadership style, motivational climate and student Machiavellianism in physical education context and c) to propose studentsâ€™ and instructorsâ€™ typology. The sample consisted of 247 Greek students (128 males, 119 females) aged 14-17 years old (M=15.4, SD=.49) from secondary schools who completed four types of questionnaires during physical education classes. The results supported the internal consistency of the instruments. Statistically significant differences were observed in instructorsâ€™ verbal aggressiveness, autocratic leadership teaching style, democratic leadership style and studentsâ€™ Machiavellianism between the two genders of the students. Perceived instructorsâ€™ verbal aggressiveness was negatively related to their democratic teaching style and mastery climate. Also, there was a positive significant relationship between instructorsâ€™ verbal aggressiveness and autocratic teaching style, performance climate and studentsâ€™ Machiavellianism. The results of regression analysis revealed that perceived instructorsâ€™ verbal aggressiveness could significantly predict the variables of leadership teaching style, motivational climate and studentsâ€™ Machiavellianism. Distinct types of relations between students and instructors may be distinguished: the â€œinsurrectionâ€, the â€œacceptance of authoritarianismâ€ and the â€œeffective democracyâ€. The findings and the effects of the instructorsâ€™ verbal aggressiveness on leadership style, motivational climate and studentsâ€™ Machiavellianism are further discussed and future research issues are suggested.